Análisis y estructuración de las creencias que tienen sobre la matemática estudiantes de básica secundaria del liceo femenino mercedes Nariño (2018)
The objective of this work was to describe the beliefs about the mathematics of a group of twelve students of IED Liceo Femenino Mercedes Nariño, a public school in the city of Bogotá, belonging to the eighth, ninth and tenth grades, and to deepen on the way they have been educated.